HADITS TENTANG KEUTAMAAN MENUNTUT ILMU DALAM ISLAM - Marlina Marlina (Adisam Publisher, 2025)
Science plays a big role in a person's life, because with science, humans can be useful for their families and their surroundings. Science is also a guideline to guide us in the right direction and can lead us to a happy life in this world and the hereafter and become a light that illuminates human life so that they do not lose their way. Humans can distinguish between right and wrong through science, so that they can understand their obligations as pious humans who carry out all His commands and avoid His prohibitions. Then Allah SWT will elevate the status of humans in this world and in the hereafter. Science plays an important role for humans. Humans will not live better without having knowledge. Therefore, let's use our time as best we can to seek useful knowledge. The obligation to seek knowledge has been explained in the Quran and Hadith. Learning is an obligation for every human being, because it is useful for increasing one's potential. Humans can find out insights that were previously not understood. So we as Muslims should pay attention to learning, because the virtues of those seeking knowledge in Islam are known.